2003
DOI: 10.4049/jimmunol.170.10.5008
|View full text |Cite
|
Sign up to set email alerts
|

Superantigen-Induced Regulatory T Cells Display Different Suppressive Functions in the Presence or Absence of Natural CD4+CD25+ Regulatory T Cells In Vivo

Abstract: Repeated exposures to both microbial and innocuous Ags in vivo have been reported to both eliminate and tolerize T cells after their initial activation and expansion. The remaining tolerant T cells have been shown to suppress the response of naive T cells in vitro. This feature is reminiscent of natural CD4+CD25+ regulatory T cells. However, it is not known whether the regulatory function of in vivo-tolerized T cells is similar to the function of natural CD4+CD25+ regulatory T cells. In this study, we demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 75 publications
2
44
1
Order By: Relevance
“…injections of SEB to mice result in development of T cells with regulatory function [21,22] and increased in vitro suppressive capacity of isolated Treg [23] as well as increased serum levels of the cytokine IL-10 [22], which is known to down-regulate T-cell activation. CD4 1 T cells from mice injected with SEA are about threefold more potent suppressors of SEA-induced T-cell proliferation and IL-2 production compared with natural CD4 1 CD25 1 Treg from untreated mice [23]. However, in the present study, we could not detect any increase in the number of T cells with regulatory phenotype in mice pre-treated with SEA, at least not 4 wk after SEA treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…injections of SEB to mice result in development of T cells with regulatory function [21,22] and increased in vitro suppressive capacity of isolated Treg [23] as well as increased serum levels of the cytokine IL-10 [22], which is known to down-regulate T-cell activation. CD4 1 T cells from mice injected with SEA are about threefold more potent suppressors of SEA-induced T-cell proliferation and IL-2 production compared with natural CD4 1 CD25 1 Treg from untreated mice [23]. However, in the present study, we could not detect any increase in the number of T cells with regulatory phenotype in mice pre-treated with SEA, at least not 4 wk after SEA treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We have not noted any untoward effect of such colonisation, as parents report no increased prevalence of gastro-intestinal or other symptoms [17]. Quite unexpectedly, we instead found that infants colonised in the first week(s) of life with S. aureus had significantly decreased risk of developing food allergy [20].Animal experiments indicate that parenteral administration of S. aureus superantigen may promote development and functional activity of Tregs [21][22][23]. The present study is designed to test the hypothesis that mucosal exposure to S. aureus superantigen in neonatal life would enhance the capacity to develop oral tolerance to a specific antigen and thereby protect against later hypersensitivity to the same antigen.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…It has been shown that, although the majority of CD4 ϩ CD25 ϩ T cells are generated in the thymus, T cells with regulatory capacities may be generated or experimentally induced in the periphery (2)(3)(4). In vitro, CD4 ϩ T cells stimulated by their cognate Ag in the presence of IL-10 can also generate T cells with regulatory properties (5).…”
Section: Immune Regulation By Self-reactive T Cells Ismentioning
confidence: 99%
“…In the present study, we have exploited a double-transgenic model that is unique in that it generates a peripheral population of self-reactive hemagglutinin (HA) 3 -specific T cells that have been shown to regulate, both in vivo and in vitro, immune responses by naive T cells expressing the same TCR (4,12). Such regulatory T cells derived from TCR-HA ϫ IG-HA double-transgenic mice share several common features with other regulatory T cells described in the literature: they are anergic in terms of proliferative capacity, they secrete IL-10 (13), and they express high levels of CTLA4 and PD1 molecules (14) as well as glucocorticoid-induced TNF mRNA (A. Sarukhan, unpublished results).…”
Section: Immune Regulation By Self-reactive T Cells Ismentioning
confidence: 99%